Fundamentals of ground improvement engineering - Evans, Jeffrey C.; Elton, David J.; Ruffing, Daniel (Abingdon, Oxon ; Boca Raton, FL : CRC Press, 2021)
"This textbook addresses the current ground improvement techniques and also suits professionals. It introduces key methods, with the underpinning theory, design principles, and construction approaches. It contains numerous problems and worked examples, and a companion website providing instructor resources and videos of the techniques"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Soil stabilization